TEKNOLOGI TEPAT GUNA PADA INDUSTRI VIRGIN COCONUT OIL DENGAN PRINSIP ZERO WASTE - Widyasari, R.; Kurniawan, H.; Hidayat, A. F.; Paramartha, D. N. A. (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i01.p01, 2021)
The coconut industry is one of the leading industries in North Lombok, in the form of raw materials, copra, as well as coconut oil and Virgin Coconut Oil (VCO). In producing VCO, the resulting waste is still economically valuable, but partners only sell it as animal feed. Even though with a touch of innovation, VCO waste can be a very high added value, namely as desiccated coconut or dry shredded coconut. The development of VCO by-product is implemented by partners using proper food processing according to SNI 7381-2008 - coconut oil and SNI 01-3715-1995 - the quality of dry grated coconut and plays a role in zero waste so that it can be marketed in quality. The method applied is to provide education on good food processing methods and conduct training on the application of appropriate technology in VCO processing and by-product processing, training on the application of packaging technology, labeling, and storage techniques, and training in business management and marketing strategies. The results felt by partners through this activity were the partners' understanding and skills regarding processing coconut dregs from VCO to desiccated coconut increased through the technology package offered. In the situation of the Covid-19 pandemic by implementing health protocols, this program can run smoothly thanks to excellent cooperation and contributions by partners.   Keywords: Coconut, VCO, Zero Waste